2016
DOI: 10.9790/0853-1508096975
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic Management of Congenitally Missing Lateral Incisors With Single Tooth Implants: A Case Report

Abstract: Congenitally missing teeth are frequently presented to the dentist. Interdisciplinary approach may be needed for the proper treatment plan. Several treatment options exist for the replacement of congenitally missing lateral incisors.This case report addresses the fundamental considerations related to replacement of a congenitally missing lateral incisor by a team approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…There was a higher average attractive smile (59%), followed by an attractive good smile (23%) and a less attractive bad smile (18%). (Muhamad, Nezar and Azzaldeen, 2016)] showed that very short and very long maxillary lateral incisors were consistently perceived as " least attractive " smiles. In [ (Shaw, 1981)] study, it shows that normal dental appearance would be judged to be better looking, more desirable as friends, more intelligent, and less likely to behave aggressively.…”
Section: Resultsmentioning
confidence: 99%
“…There was a higher average attractive smile (59%), followed by an attractive good smile (23%) and a less attractive bad smile (18%). (Muhamad, Nezar and Azzaldeen, 2016)] showed that very short and very long maxillary lateral incisors were consistently perceived as " least attractive " smiles. In [ (Shaw, 1981)] study, it shows that normal dental appearance would be judged to be better looking, more desirable as friends, more intelligent, and less likely to behave aggressively.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 33 ] Osseo-integrated implants can, also, be used to replace congenitally missing maxillary lateral incisors. [ 34 35 36 37 ] Customized lingual orthodontic appliances and adjunctive use of direct skeletal anchorage derived from two palatal mini-implants have, also, been successfully used in patients to close the space of congenitally missing lateral incisors. [ 38 ] The review of the literature suggests that orthodontic space closure in missing laterals produced stable results and were accepted better by patients compared to prosthetic rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The replacement of a damaged adult tooth by the insertion of dental implant material cannot be overemphasized in the treatment of dental ailments in the world today. In children, this thermal treatment method has not been considered seriously, and the use of implants is still infrequent and controversial [14] . In some cases, anodontia, partial anodontia, congenitally missing teeth, and tooth loss from accident or trauma occur in children and adolescents, and they may undergo dental implantation with a dental implant that would be thoroughly scrutinized to suit the body system and growth rate of the patient.…”
Section: Childhoodmentioning
confidence: 99%